Simulation and Haptic Devices in Engineering Education - Lopes, D.; Vaz de Carvalho, C. (Elektronika ir Elektrotechnika, 2010)
This article describes one methodology to integrate haptic devices in education, providing a new and innovative learning method. Examples of the methodology are given: the study of flight aerodynamics with resource to a low-cost haptic device - a tactile sensory interface between a person and a computer. A wind tunnel is the scenario depicted in the simulation and the interface shows a P-38 Lightning plane (from World War II). Students see a scheme that represents the magnitude of the four aerodynamic forces and data on speed, angle of attack and status of the airplane, which tells if the airplane is on the take-up, and so on. The resultant of the forces is "felt" by the user through the haptic mechanism. The system has been applied to first year Engineering students in a case study experiment to validate the learning methodology. In the end their knowledge was tested and their perception on the relevance and interest of the system was evaluated. Results show that physics understanding was greatly enhanced and that students motivation for learning, even theoretical aspects and concepts, was increased.